Musikalsk nasjonsbygging - Hylland, Ole Marius; Stavrum, Heidi (Tidsskrift for kulturforskning, 2018)
In this article, we discuss the music policy of Arts Council Norway in the period 1965-2015. Our starting point is that the music policy of Council is an example of musical nation building. Through the schemes and projects of the Arts Council, the boundaries of the musical nation have been drawn up, maintained and redefined in various ways that have had both aesthetic, institutional and organizational consequences. The Arts Council's music policy is about building a country, building a music life, and building a people. It is about musical nation building in dual sense: both building a nation with the help of music, as well as building a music nation. This project has been challenged by the redefinition of two types of boundaries: aesthetic boundaries and geographical boundaries. From being an artistic building project within a safe national framework, music policy has evolved to be characterized by both aesthetic, geographical and cultural diversity. At the same time, the national element has far from disappeared. The musical nation building is not a completed project.